Analisis Kinerja Pajak Dan Retribusi Daerah Kota Ternate : Pendekatan Data Envelopment Analysis (DEA): (Performance Analysis of Local Taxes and Levies in Ternate City: Data Envelopment Analysis (DEA)) - Laela Mustafa; Chairullah Amin; Mohammad Kotib (UPT Penerbitan Universitas Jember, 2023)
The research aims to measure the performance of regional taxes and levies in economic development in Ternate City. The study uses the data envelopment analysis (DEA) method by comparing DMUs based on a large number of inputs to produce the expected output. The DMU used is the regional tax and levy management body of Ternate City. The indicators in this research consist of (1) two inputs and one output, (2) nine inputs and one output, and (3) 13 inputs and one output. The data used is a report on the realization of Ternate City regional income receipts for 2012-2021 which consists of regional taxes and levies. The data was analyzed using the DEAP version 2.1 application with the Constant Returns to Scale (CRS) model. The results show that in the CRS model, there are two years of PAD output that have efficient performance, while the tax output and levy output both have efficient performance for 10 years.